2020
DOI: 10.1371/journal.pone.0230053
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety: An overlooked confounder in the characterisation of chronic stress-related conditions?

Abstract: Although anxiety disorders are among the most prevalent of psychiatric disorders, childhood trauma-related studies seldom consider anxiety proneness as distinct aetiological contributor. We aimed to distinguish between trauma-and anxiety-associated physiological profiles. South African adolescent volunteers were categorised for trauma exposure (CTQ, mean score 39±11) and anxiety proneness (AP)(CASI, mean score 37±7, STAI-T, mean score 41 ±8). Circulating hormone and leukocyte glucocorticoid receptor levels, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Viljoen et al [53] indicate that DHEA has significant predictive power in the context of propensity to anxiety and propose it as a biomarker to monitor progressive changes related to anxiety in the HPA axis. In this context, we observed that the levels of cortisol decreased together with the anti-stress hormone DHEA as well [54,55].…”
Section: Stress and Anxiety In The Studied Ed Professionalsmentioning
confidence: 99%
“…Viljoen et al [53] indicate that DHEA has significant predictive power in the context of propensity to anxiety and propose it as a biomarker to monitor progressive changes related to anxiety in the HPA axis. In this context, we observed that the levels of cortisol decreased together with the anti-stress hormone DHEA as well [54,55].…”
Section: Stress and Anxiety In The Studied Ed Professionalsmentioning
confidence: 99%
“…Fourth, SAD is often unrecognized and diagnosed as another affective disorder [151], making it difficult to collect reliable samples of patients. Finally, different studies did not take into account confounding factors such as environmental variables [152], psychiatric and medical comorbidities [153] and medications [154]. Nevertheless, most studies were rated as of moderate quality [32].…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with a propensity for anxiety, there is an increase in the expression of glucocorticoid receptors and lower levels of dehydroepiandrosterone (DHEA), a hormone with anti-anxiety properties. Moreover, anxious and traumatized individuals exhibit reduced production of the anti-inflammatory cytokine IL-10 [18]. Anxiety symptoms often co-occur with deficits in emotional attention control.…”
Section: Hpa Axismentioning
confidence: 99%